2020
DOI: 10.1017/s0007114520004961
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study of factors associated with height-for-agez-scores of children aged 6−23 months in northwest Rwanda: the role of care practices related to child feeding and health

Abstract: We aimed to identify the factors influencing child height-for-age z-scores (HAZ) as a measure of child nutritional status in Rwanda, and to examine the role of child feeding and health practices. We conducted a cross-sectional study involving 379 children (aged 6–23 months) and their mothers in northwest Rwanda. Data were collected using a pre-tested, structured questionnaire. An infant and young child feeding practices index (ICFI) and health practices index (HPI) were developed and categorised into tertiles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
3
3
1
Order By: Relevance
“…The prevalence of underweight and wasting in this study was lower than in studies in Indonesia (26 and 23%, respectively) ( 51 ) and India (43.4 and 43.7%, respectively) ( 50 ). The stunting in this study was lower than in a study in Rawad (39%) ( 52 ), but higher than in studies in Indonesia (28%) ( 51 ), Mongolia (6.3%) ( 14 ), and rural areas of China (7.1%) ( 53 ). Wasting in this study was also higher than in studies in Tanzania (6%) ( 48 ) and rural areas of China (3.0%) ( 53 ).…”
Section: Discussioncontrasting
confidence: 83%
“…The prevalence of underweight and wasting in this study was lower than in studies in Indonesia (26 and 23%, respectively) ( 51 ) and India (43.4 and 43.7%, respectively) ( 50 ). The stunting in this study was lower than in a study in Rawad (39%) ( 52 ), but higher than in studies in Indonesia (28%) ( 51 ), Mongolia (6.3%) ( 14 ), and rural areas of China (7.1%) ( 53 ). Wasting in this study was also higher than in studies in Tanzania (6%) ( 48 ) and rural areas of China (3.0%) ( 53 ).…”
Section: Discussioncontrasting
confidence: 83%
“…From random effects model estimate, the pooled odds of developing stunting was higher among children who received less than four food score than children who provided greater than four varieties of food items which is similar to a study in Rwanda [ 19 , 20 ]. If Children did not feed the recommended diversified food in their life window, it is inevitable to be exposed for stunted growth, development, morbidity and mortality.…”
Section: Discussionsupporting
confidence: 75%
“…Several studies indicated that various factors contribute to the developments of stunting in less than 24 months children. For example, maternal age [ 14 , 15 ], maternal education [ 16 ], child age [ 17 ], having more than one child under 2 years of age in the household [ 18 ], minimum dietary diversity, consumption of animal sourced food, child’s sex [ 19 ], diarrhea, respiratory infection [ 20 ], lower wealth quintile [ 21 ], household dietary diversity, early initiation of complementary feeding [ 22 ] are some of the associated factors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, knowledge about the benefits of breastfeeding is key to ensuring proper nutrition in the first months of life. Targeting these practices enables families to provide diverse and nutritious foods for their children and to make more health-promoting prioritizations when necessary [56]. Climate change is an external factor that threatens food security, exacerbating any negative effect of poor household wealth or improper feeding practices.…”
Section: Discussionmentioning
confidence: 99%